Niels Bohr, 1913-2013 Poincaré Seminar 2013 - Darrigol, Olivier; Duplantier, Bertrand; Raimond, Jean-Michel; Rivasseau, Vincent (Progress in Mathematical Physics, 2016)
This fourteenth volume in the Poincaré Seminar Series is devoted to Niels Bohr, his foundational contributions to understanding atomic structure and quantum theory and their continuing importance today. This book contains the following chapters: - Tomas Bohr, Keeping Things Open; - Olivier Darrigol, Bohr's Trilogy of 1913; -John Heilbron, The Mind that Created the Bohr Atom; - Serge Haroche & Jean-Michel Raimond, Bohr's Legacy in Cavity QED; - Alain Aspect, From Einstein, Bohr, Schrödinger to Bell and Feynman: a New Quantum Revolution?; - Antoine Browaeys, Interacting Cold Rydberg Atoms: A Toy Many-Body System; - Michel Bitbol & Stefano Osnaghi, Bohr´s Complementarity and Kant´s Epistemology. Dating from their origin in lectures to a broad scientific audience these seven chapters are of high educational value. This volume is of general interest to physicists, mathematicians and historians.